'Bakhtinian Contextuality' in Adaptation Studies: Screen Robinson Subverting the Source. (8th July 2016) - Öz, Seda
Abstract: Since soon after the publication of Daniel Defoe's 1719 novel Robinson Crusoe, there have been many different cinematic and literary adaptations of this famous adventure story, which are collectively known as 'Robinsonades'. Due to the plastic nature of the Robinson Crusoe story, which is a function of what Mikhail Bakhtin defines as the 'adventure chronotope', there are many intra-medial and inter-medial adaptations of Defoe's novel in different historical, cultural, social, and ideological contexts in which the 'dominant' and/or 'emergent' 'structures of feeling' are represented. This article furthers the exploration of the adaptability of Defoe's Robinson Crusoe by illustrating the central argument with reference to an inter-medial adaptation of the Robinson Crusoe story. Following a brief account of what may be termed as the 'Bakhtinian contextuality' with reference to the contemporary adaptation studies scholars, Bakhtin's ideas on 'chronotope' and 'adventure time', and their relationship with the Robinson Crusoe story and the Robinsonade tradition and the main methodological approach that is used in analysing these adaptations will be explained.